Pengaruh Akuntabilitas Keuangan dan Pengendalian Internal di Gereja HKBP Jatiasih terhadap Pencapaian Program Kerja Pelayanan - Hasiholan, Andreas; Perdana, Petrolis Nusa; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This study aims to obtain the results of the influence of financial accountability and internal control on the achievement of service work programs at the HKBP Jatiasih church. The data source used is the primary data source in the form of an online form (google form) which is distributed to the HKBP Jatiasih church congregation. The sampling method was carried out with a random sample of 195 respondents which was obtained based on the sample limit on the Slvoin calculation. The data analysis method used is descriptive statistics, validity test, classic assumption test, multiple linear analysis, and hypothesis testing. The following are research results, namely: a) Financial accountability has a significant influence on the achievement of service work programs; b) Internal control has a significant positive influence on the achievement of service work programs.